(3TQM GdgGOis - (3GHi GdbGSe gHg Gddg GHf YHO Gddg GdbaWis; (3bWH GdOjf CHj GdeYGdj eSYhO Hf eMeO, GdfjSCHhQj,J (B578 (3g` s ((3CHi YHOGddg eMeO Hf gHg Gddg Hf eMeLO Hf GdMSf GdESfGhi s)
(3ChdgG (B:s
(3cJGH GdQVGY s
(3JdaJ GdChQGb GdChdi hGdCNjQI hdPdc JYPQ bQGAI YfhGf GdcJGH heDdags
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs